Strengthening the Values of Pancasila to Improve Students' Prosocial Skills in Elementary School - Zulfikri Zulfikri; Arifin Maksum; Nina Nurhasanah (Edumaspul: Jurnal Pendidikan, 2024)
The focus of the problem in this study is how: (1) the description of the strengthening of Pancasila values and the description of students’ prosocial behavior; (2) how the strengthening of Pancasila values improves students’ prosocial abilities in elementary schools. The purpose of this study was to determine: (1) the description of the strengthening of Pancasila values and the description of students’ prosocial behavior; and (2) the strengthening of Pancasila values to improve students’ prosocial abilities in elementary schools. This research uses the literature study method. The literature study research method is a research method by reading and analyzing readings related to the theme taken. The results of this study show an overview of the Pancasila values contained in the third principle, namely: (a) Bringing up a sense and attitude of mutual assistance or helping, volunteering, and increasing family attitudes; b) Fostering good social relationships with peers and adults; (c) Creating a sense of togetherness and affection, and (d) creating a sense of unity with the surrounding environment. These values are manifested in the form of value reinforcement: (a) through the learning process in class (b) Cooperation in small groups and (c) Clean Friday. Strengthening the value of Pancasila can improve prosocial abilities, namely in the dimensions of sharing, cooperation (cooperative), donating, helping, honesty, and giving (generosity).